Molecular Docking Studies of Some Hydroxy Nitrodiphenyl Ether Analogues as Tyrosinase Inhibitors - Fatemeh Sholehvar; Azizeh Asadzadeh; Hooria Seyedhosseini (Fasa University of Medical Sciences, 2016)
Background & Objective: Tyrosinase is a key enzyme in pigment synthesis.Overproduction of melanin in parts of the skin results in hyperpigmentation diseases. Thus, its inhibitors are highly important in the medical, cosmetic and agricultural fields. The aim of this research is the bioinformatical study of tyrosinase inhibition by a number of hydroxy nitrodiphenyl ether derivatives. Material & Methods: This is a descriptive-analytic study. In order to investigate the mode of interaction of the compounds with tyrosinase active site, the chemical structures of all compounds were designed using ChemDraw program, then transferred into Hyperchem software for energy minimization. Docking study was performed by AutoDock 4.2 program and the resulting docking poses were analyzed in AutoDockTools, DS Visualizer 3.5 and Ligplot software. Results: Among the all studied compounds, the best docking results were related to 4-Hydroxy- 2'-nitrodiphenyl etherdisplayed. In fact, this compound had the most negative ΔGbind (-12.79 Kcal/mol) that indicated favorable interactions with the key amino acid residues at active site of tyrosinase. Docking results for this compound are in accordance with those of co-crystallized ligand (tropolone). In this compound, the oxygen of nitro group has an efficient metal-ligand interaction with the Cu2+ ions in the active site. Conclusion: Finally, in respect to  high effectiveness and docking results, we can conclude that the compound 4-Hydroxy- 2'-nitrodiphenyl ether may be regarded as an effective anti-tyrosinase inhibitor.